Dextran sulfate triggers platelet aggregation via direct activation of PEAR1. (18th May 2016) - Vandenbriele, Christophe; Sun, Yi; Criel, Maarten; Cludts, Katrien; Van kerckhoven, Soetkin; Izzi, Benedetta; Vanassche, Thomas; Verhamme, Peter; Hoylaerts, Marc F.
Abstract: Dextran sulfate (DxS; Mr 500 kD) induces fibrinogen receptor (αIIb β3 ) activation via CLEC-2/Syk signaling and via a Syk-independent SFK/PI3K/Akt-dependent tyrosine kinase pathway in human and murine platelets. The platelet surface receptor, responsible for the DxS-induced Syk-independent Akt-activation, has hitherto not been identified. We found that DxS elicited a concentration-dependent aggregation of human platelets resulting from direct PEAR1 activation by DxS. Blocking the PEAR1 receptor, in combination with a selective Syk-inhibitor, completely abrogated the DxS-driven platelet aggregation. The DxS-induced Syk-phosphorylation was not affected in Pear1 −/− platelets, but Akt-phosphorylation was largely abolished. As a result, the aggregation of Pear1 −/− platelets was reduced and reversible, i.e. aggregates were less stable compared to wild-type platelet aggregates. Moreover, DxS-induced Pear1 −/− platelet aggregation was fully abrogated by Syk inhibition, indicating that the remaining platelet aggregation of Pear1 −/− platelets was Syk dependent. Hence, the Pear1/c-Src/PI3K/Akt- and CLEC-2/Syk-signaling pathways are independently and additively activated during platelet aggregation by DxS. Conclusion . The DxS-induced aggregation of human and murine platelets is the result of activation of PI3K/Akt through direct PEAR1 phosphorylation and parallel Syk-signaling through CLEC-2.